The Archetypal Symbols and The Hero’s Journey of Alice in Wonderland Film - Rohmatul Fitriyah Dewi; Darini Yusrina A (Surakarta English and Literature Journal, 2023)
Myth is a classic story about heroes who explain the origins of natural occurrences. Myth is not always given historically since the modern one will continue to evolve and impact cinema creation. This study aimed to look at the categorization of Campbell's "hero's journey" and the archetypal symbols under Segal's theory, as provided by the main character in the Alice in Wonderland film. The data for this study was taken from a plotline in Woolverton's Alice in Wonderland. The study's findings suggested that the film had a tight relationship with a myth. The primary characters, including Alice, the Red Queen, and the White Queen, symbolized archetypal emblems of light and evil. Alice could eventually complete the hero's journey, beginning with departure, reaching a climax in the initiation stage, and reaching the return stage as the significant point of the movie's plot and the same fundamental structure in the myths.